Arrangment of responsibility character module using expert validation - Budi Astuti; Arina Mufrihah (Intelektual Pustaka Media Utama, 2019)
This study aims to produce responsibility character module to improve student self-regulated learning. The research method uses research and development. The research subjects involved in the need assessment were 248 students of Guidance and Counseling, School of Education, Universitas Negeri Yogyakarta which was obtained by random sampling technique. Data collection using the scale of self-regulated learning. The scale of selfregulated learning is adapted from Zimmerman's theory which consists of three aspects: cognitive, motivation and behavioral aspects. Data were analyzed using mean test. The result of the need assessment is used as a reference to develop the responsibility character module to improve student self-regulated learning. This study successfully created a module of responsibility character to improve university students’ self-regulated learning which is consisted of 12 materials that had been validated and revised; therefore it is eligible to be implemented in the self-regulated learning context.